Institutional and Policy Analysis of River Basin Management : The Jaguaribe River Basin, Ceará, Brazil - Johnsson, Rosa Maria Formiga (World Bank, Washington, DC, 2012)
The authors describe and analyze water resources reform and decentralization of river basin management in the state of Ceara, Northeast Brazil, the poorest part of the country. The Jaguaribe river basin is located entirely within the state of Ceara. With a drainage area of 72,560 square kilometers, it covers almost half of the state's territory. The basin has 80 municipalities and more than 2 million people, about half rural and half urban, in primarily small towns, representing about a third of Ceara's population. Precipitation in the basin is highly variable, ranging from 400 mm in the hinterland to 1,200 mm along the coast. Rivers in the basin are ephemeral and only flow during the rainy season. The key water management challenge is to capture the water in reservoirs in rainy years and to manage it such that it will last for several years, in case the following years are drought years. The other important challenge is the increasing dependence of the state capital Fortaleza, located in a different basin, on water from the Jaguaribe basin. Decentralization of decisionmaking has taken place at two levels. Devolution from the federal to the state level in the past 15 years was highly successful. The state has created its own Water Resources Management Company (COGERH) which is responsible for water resources management throughout the state. Decentralization from state to local level has been more partial. Although COGERH has decentralized the allocation of strategic reservoir waters to local institutions, many traditional water management attributions continue under its and the state's purview, such as water permits, bulk water pricing, planning, operation and maintenance of hydraulic infrastructure, groundwater management, and control. The creation of sub-basin committees and user commissions has increased stakeholder participation of all types. Although so far stakeholder involvement has been limited largely to the negotiated allocation of water and to conflict resolution, these experiences represent a radical transformation in management practices, transforming water users from uninformed takers of water management decisions to informed and aware participants in the management process. That said, local stakeholders still have no say in some decisionmaking processes that affect them directly, such as bulk water pricing or inter-basin transfers to Greater Fortaleza, which continue solely under the control of state government agencies. The case of the Jaguaribe basin shows that (1) long-standing political support is of major importance in the development and implementation of water resources management reform, (2) that institutional arrangements for water resources management can successfully be adapted to local conditions to achieve positive outcomes, and (3) that even with initial conditions that seem to not favor change, decentralization can be achieved.